Evaluating Recruitment Strategies for a Randomized Clinical Trial with Heart Failure Patients. (August 2021) - Conley, Samantha; O'Connell, Meghan; Linsky, Sarah; Moemeka, Lesa; Darden, James W.; Gaiser, Edward C.; Jacoby, Daniel; Yaggi, Henry; Redeker, Nancy S.
Recruiting participants with chronic medical conditions is time-consuming and expensive. Electronic medical record databases and patient portals may enable outreach to larger numbers of patients in comparison to face-to-face methods. We aimed to describe the yields, benefits, and limitations of recruitment strategies used for a randomized clinical trial of cognitive behavioral therapy for insomnia among patients with chronic stable heart failure (NCT02660385). We used multiple recruitment strategies including clinic-based recruitment, letters to patients identified from electronic databases, the patient portal, brochures and posters placed in clinics, presentations to heart failure support groups, and online advertising. We screened 10, 291 medical records, enrolled 231 participants, and 195 participants completed baseline data collection. We enrolled 92 (23%) participants using clinic-based recruitment, 24 and 29 (6% and 10%) using letters to patients from two electronic databases, and 42 (55%) via the patient portal. Multiple recruitment strategies and flexibility are needed to achieve recruitment goals.